Enhancing students on climate issues through social media marketing and green knowledge sharing: A contemporary da'wah approach in Indonesia and Turkey - Sutopo; Nur Hendrasto; Afif Zaerofi; Haidar, Abdullah (Jurnal Ilmu Dakwah, 2025)
Purpose - This study examines the influence of social media marketing and green knowledge sharing on climate change awareness among university students in Indonesia and Turkey. These digital initiatives are framed as a contemporary form of da'wah bil hal, where Islamic values of environmental stewardship are promoted through action-based communication and active engagement on social media platforms. Method - A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 327 students through purposive sampling. Result  -  The findings reveal that social media marketing significantly impacts green knowledge sharing (β = 0.279, p = 0.016) and climate awareness (β = 0.305, p = 0.012), with green knowledge sharing mediating the relationship (β = 0.112, p = 0.038). However, climate awareness alone does not significantly lead to pro-environmental behavior. Implication – The study highlights that empowering students through social media campaigns can be an effective strategy for environmental da'wah, integrating Islamic values into climate action. Originality/Value - This study is one of the first cross-cultural investigations linking social media-driven environmental communication with Islamic da'wah practices between Indonesia and Turkey. It highlights cultural variations in environmental awareness and communication style, where Indonesian students show higher collectivist-driven engagement in green campaigns. In contrast, Turkish students tend to approach environmental messaging more individually. These contrasts enrich understanding of how Islamic da'wah bil hal can be contextualized across different cultural and educational settings. *** Tujuan - Studi ini bertujuan untuk menganalisis pengaruh pemasaran media sosial dan berbagi pengetahuan hijau terhadap kesadaran perubahan iklim di kalangan mahasiswa universitas di Indonesia dan Turki. Inisiatif digital ini dikonsepkan sebagai bentuk kontemporer dari da'wah bil hal, di mana nilai-nilai Islam tentang pengelolaan lingkungan dipromosikan melalui komunikasi berbasis aksi dan keterlibatan aktif di platform media sosial. Metode - Pendekatan kuantitatif digunakan dengan menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) untuk menganalisis data yang dikumpulkan dari 327 mahasiswa melalui sampling purposif. Hasil  -  Temuan menunjukkan bahwa pemasaran media sosial secara signifikan mempengaruhi berbagi pengetahuan hijau (β = 0.279, p = 0.016) dan kesadaran iklim (β = 0.305, p = 0.012), dengan berbagi pengetahuan hijau sebagai mediator dalam hubungan tersebut (β = 0.112, p = 0.038). Namun, kesadaran iklim sendiri tidak secara signifikan mengarah pada perilaku pro-lingkungan. Implikasi – Studi ini menyoroti bahwa memberdayakan mahasiswa melalui kampanye media sosial dapat menjadi strategi efektif untuk da'wah lingkungan, dengan mengintegrasikan nilai-nilai Islam ke dalam aksi iklim. Orisinalitas/Nilai - Studi ini merupakan salah satu penelitian lintas budaya pertama yang menghubungkan komunikasi lingkungan berbasis media sosial dengan praktik da'wah Islam antara Indonesia dan Turki. Studi ini menyoroti variasi budaya dalam kesadaran lingkungan dan gaya komunikasi, di mana mahasiswa Indonesia menunjukkan keterlibatan yang lebih tinggi didorong oleh kolektivisme dalam kampanye hijau. Sebaliknya, mahasiswa Turki cenderung mendekati pesan lingkungan secara lebih individual. Perbedaan ini memperkaya pemahaman tentang bagaimana da'wah bil hal Islam dapat dikontekstualisasikan dalam berbagai setting budaya dan pendidikan.